ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS V DALAM MENYELESAIKAN SOAL DI SD NEGERI GUNTURAN PANDAK BANTUL TAHUN AJARAN 2016/2017 - Inna Rohmatun Kholidah; A. A Sujadi (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract: The purpose the research to describe the understanding of mathematical concepts about solid. Questions research to know Percentage re-explain concept, to know Percentage classify and give example / non example, also to know Percentage utilizing count operation. Type of research quantitative description, subject of the research is students of grade V SD Negeri Gunturan and the object is understanding of mathematical concepts. Data analysis techniques performed at problem solving were analyzed with 3 indicators of understanding of mathematical concepts 3 indicator concept understanding are re-explaining concepts, classifying and giving examples, utilizing counting operations. Result research of understanding concepts 50,91% low category. Percentage of re-explain the concept of 68.35% height. Percentage classify and give example / non example 50.80% medium category. Percentage utilizing count operation 33.59% low category.